Randomized trial on the effects of an EMDR intervention on traumatic and obsessive symptoms during the COVID-19 quarantine: a psychometric study - Miccoli, Mario; Poli, Andrea (Frontiers in Psychiatry, 2024)
It has been suggested that the COVID-19 pandemic is a potentially traumatic occurrence that might induce generalized anxiety and discomfort, particularly in susceptible populations like individuals with mental illnesses. The therapeutic approach known as eye movement desensitization and reprocessing (EMDR) has shown to be successful in helping patients processing traumatic events and toward wellbeing restoration. Nevertheless, little is known about the precise processes through which EMDR fosters symptoms recovery. In order to disentangle these issues, we conducted a randomized controlled trial (ClinicalTrials.gov Identifier NCT06110702) with 107 participants who were selected from university hospitals as a sample of investigation. Random assignments were applied to the participants in order to assign them to the experimental and control groups. The experimental group, but not the control group, underwent a eight-week EMDR intervention. Body perception, disgust, guilt and shame emotions, as well as mental contamination and post-traumatic and obsessivecompulsive symptoms were investigated before and after the EMDR intervention. The EMDR intervention was able to improve all of the variables investigated. Path analysis showed that body perception was able to predict both disgust and guilt and shame emotions. Disgust was able to predict both mental contamination and obsessive-compulsive symptoms, while guilt and shame were able to predict post-traumatic symptoms. Implications for clinical practice are examined.